Java: The Complete Reference, Thirteenth Edition - Schildt, Herbert; Coward, Danny (McGraw Hill LLC, 2024)
The definitive guide to Java programming-thoroughly revised for Java SE 21Fully updated for the current version of Java, Java SE 21, this comprehensive guide shows, step by step, how to design, write, debug, run, and administer high-performance Java programs. Inside, bestselling author Herbert Schildt and programming expert Dr. Danny Coward cover the entire Java language, including its syntax, keywords, and libraries. The book lays out cutting-edge development techniques and best practices.Java: The Complete Reference, Thirteenth Edition features clear explanations, detailed code samples, and real-world examples that demonstrate how Java can be put to work in the real world. JavaBeans, servlets, applets, Swing, lambda expressions, multithreading, and the default interface method are thoroughly discussed. You will get full details on all of the latest features and changes in JDK 18 through long-term support (LTS) release JDK 21.Designed for novice, intermediate, and professional programmers alikeSource code for all examples and projects are available for downloadWritten in the clear, uncompromising style Herb Schildt is famous for